Church and state in Spain in 1999 - Motilla, Agustín (European journal for church and state research, 2000)
Abstract der Zeitschrift: Another year has gone by without significant legislative reforms. We can only point to the modifications in the procedure in obtaining civil effects of the canonical resolution of nullity or non-consummated marriage that are included in the Civil Proceeding Act recently put into effect